Aktifitas Fisik, Riwayat Dismenore Keluarga dan Kecemasan dengan Dismenore pada Remaja - Elis Diana Putri; Aprilya Nency (MPI Press, 2021)
Introduction: Menstrual pain problems are problems that are often complained of by women, especially during their teens. This condition can get worse if accompanied by unstable psychological conditions, such as stress, depression, excessive anxiety, and excessive sadness or happiness. Objectives: The purpose of this study was to determine the relationship of physical activity, family history of dysmenorrhea and anxiety with dysmenorrhea in adolescents at SMK Wijaya Kusuma, South Jakarta in 2020. Method: The design of this study used analytical methods with cross sectional research designs. The population of this research is the Young Women at Smk Wijaya Kusuma. So the sample needed is 86 respondents. Result: Chi square hypothesis test results obtained p-value of 0.035, it can be concluded that there is a relationship between physical activity and dysmenorrhea in adolescents at SMK Wijaya Kusuma, South Jakarta in 2020. In addition, an Odds Ratio (OR) score of 3.874 means that respondents routinely perform physical activity had 3,874 times the chance to experience mild dysmenorrhea compared with respondents who did not routinely engage in physical activity. There is a relationship of anxiety towards dysmenorrhea in adolescents in Smk Wijaya Kusuma, South Jakarta in 2020 with a p-value of 0.012 and an Odds Ratio (OR) of 3.539. Conclution: The conclusion is that there is a relationship between physical activity, family history of dysmenorrhea and anxiety with dysmenorrhea in adolescents at SMK Wijaya Kusuma, South Jakarta in 2020. Suggestions for adolescents to be able to routinely carry out daily physical activities such as exercising and doing homework in order to reduce dysmenorrhea.